Platelet CD40 contributes to enhanced monocyte chemoattractant protein 1 levels in patients with resistant hypertension. (June 2016) - Stumpf, Christian; Raaz, Dorette; Klinghammer, Lutz; Schneider, Markus; Schmieder, Roland E.; Garlichs, Christoph D.; Achenbach, Stephan
Abstract: Background: Growing evidence shows that inflammation plays a pivotal role in the pathophysiology of essential hypertension (EH). Although it is acknowledged that target organ damage involves an inflammatory response, most work has focused on the role of macrophages. However, recently, platelets were identified as inducing inflammation partly by releasing cytokines. The goal of our study was to evaluate the role of platelets as inflammatory cells in the pathogenesis of EH. Methods: Thirty‐nine patients with EH and 30 healthy normotensive controls have been examined. Expression of platelet CD40 was measured by flow cytometry. Serum levels of monocyte chemoattractant protein 1 (MCP‐1) and sCD40L were measured via a multiplexing assay. In in vitro experiments, activated platelets were cocultured with human umbilical vein endothelial cells (HUVEC) in the presence and absence of anti‐CD154 antibodies. MCP‐1 in the supernatants was measured by EIA. Results: Essential hypertension patients showed significantly enhanced MCP‐1 levels with highest levels in EH patients with microalbuminuria. EH patients showed increased expression of platelet CD40. In the cell coculture model, activated platelets were able to significantly induce MCP‐1 release from HUVEC in a CD40L‐dependent manner. EH patients showed elevated sCD40L levels with a positive correlation with MCP‐1 levels. Conclusions: Platelets can contribute to enhanced MCP‐1 levels in EH. MCP‐1 is markedly elevated in serum of EH patients with highest levels in patients with microalbuminuria, one early sign of renal target organ damage. Further studies are required to test whether MCP‐1 blocking or antiplatelet strategies may represent new therapeutic options in preventing hypertensive target organ damage.